Biochemical and molecular responses of hot pepper (Capsicum annuum) to cold stress - MANGAL, MANISHA; SRIVASTAVA, ARPITA; SINGH, KHUSHBOO; KUMARI, SHILPI; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2022)
Four cold tolerant hot pepper (Capsicum annuum L.) genotypes were identified at Division of Vegetable Science, ICAR-IARI, New Delhi which showed significantly better agronomic performance during the cold winter conditions of Delhi during 2019–20 when most of other genotypes succumbed. Present investigations were carried out to understand the biochemical and molecular basis of cold tolerance in these genotypes for which they were compared with cold sensitive genotypes for various biochemical parameters as well as for expression of some cold inducible genes. The results indicated that the cold tolerant genotypes had inherent biochemical and molecular mechanism which helped them in cold acclimation. These genotypes had strong antioxidant defense and ROS (Reactive Oxygen Species) scavenging system as displayed by significantly high activities of guaiacol-peroxidase and superoxide dismutase and lower levels of lipid peroxidation in response to cold stress. They also accumulated higher concentration of proline to maintain their membrane fluidity and H2O2. Twelve of the fourteen cold inducible genes studied in the present investigations had significantly high expression in cold tolerant genotypes. However the expression profile of these genes differed in different genotypes indicating that mechanism of cold tolerance was not identical in all the genotypes. The confirmation of existence of innate cold tolerance mechanism in our test genotypes can pave a way for future utilization of these genotypes in cold stress breeding.